Metastatic Recurrence of Typical Pulmonary Carcinoid Accompanied by Carcinoid Syndrome, Successfully Treated with Octreotide LAR. (28th December 2017) - Yanagisawa, Asako; Hirano, Satoshi; Shimizu, Shinichiro; Hiroishi, Takuma; Shikano, Kohei; Hayama, Noriko; Fujita, Tetsuo; Amano, Hiroyuki; Nakamura, Makoto; Nakamura, Sukeyuki; Tabeta, Hiroshi
Abstract : We present a case of metastatic recurrence of carcinoid tumor accompanied by carcinoid syndrome in a 68-year-old Japanese man, 12 years after resection of typical pulmonary carcinoid. Histopathologic examination from percutaneous liver biopsy revealed metastatic typical carcinoid. Clinical symptoms gradually improved after administration of octreotide LAR. Two years after starting treatment, the disease remains well controlled. This case report illustrates the possibility of antiproliferative effects of octreotide LAR on typical pulmonary carcinoid.